PENGARUH PENGGUNAAN CHATGPT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATA PELAJARAN EKONOMI - Renita; Hamka; Emmi Azis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing use of ChatGPT among students highlights the need to examine its impact on the learning process. This study aims to determine the effect of ChatGPT use on students’ problem-solving abilities in Economics among Grade X students at SMA Negeri 7 Bone. This study employed a quantitative approach using an ex post facto research design. The sample consisted of 50 students selected through purposive sampling. Data were collected using questionnaires and documentation and were analyzed using simple linear regression with the assistance of SPSS. The results showed that the t-value of 4.530 was greater than the t-table value of 1.677, with a significance value of 0.000 < 0.05, indicating that H₁ was accepted. The regression equation obtained was Y = 32.304 + 0.664X. The positive regression coefficient indicates that increased use of ChatGPT is associated with improved students’ problem-solving abilities. The R Square value of 0.300 indicates that ChatGPT use contributes 30.0% to the variation in students’ problem-solving abilities, while the remaining 70.0% is influenced by other factors outside the model. Therefore, the use of ChatGPT has a positive and significant effect on the problem-solving abilities of Grade X students in Economics at SMA Negeri 7 Bone.